2017
DOI: 10.1007/s10126-017-9772-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Heritability for Growth and Shell Color Traits and Their Genetic Correlations in the Black Shell Strain of Pacific Oyster Crassostrea gigas

Abstract: The Pacific oyster Crassostrea gigas has been introduced widely and massively and became an economically important aquaculture species on a global scale. We estimated heritabilities of growth and shell color traits and their genetic correlations in black shell strain of C. gigas. Analyses were performed on 22 full-sib families in a nested mating design including 410 individuals at harvest (24 months of age). The parentage assignment was inferred based on four panels of multiplex PCR markers including 10 micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 36 publications
6
14
1
Order By: Relevance
“…Other studies have reported heritability estimates for weight ranging from 0.1 to 0.5 in C. gigas ( Hedgecock et al, 1991 ; Sheridan, 1997 ; Langdon et al, 2003 ; Evans and Langdon, 2006 ). Our results are consistent with heritability estimates described for shell measurements, e.g., Li et al (2011) reported values of 0.149–0.402 for SH in C. gigas at 12 months of age, while Kong et al (2015) described estimates of 0.49 for SH and 0.36 for SL, and Xu et al (2017) reported heritability values of 0.18 for SH and 0.25 for SL. These results imply that growth can potentially be improved by selective breeding.…”
Section: Resultssupporting
confidence: 91%
“…Other studies have reported heritability estimates for weight ranging from 0.1 to 0.5 in C. gigas ( Hedgecock et al, 1991 ; Sheridan, 1997 ; Langdon et al, 2003 ; Evans and Langdon, 2006 ). Our results are consistent with heritability estimates described for shell measurements, e.g., Li et al (2011) reported values of 0.149–0.402 for SH in C. gigas at 12 months of age, while Kong et al (2015) described estimates of 0.49 for SH and 0.36 for SL, and Xu et al (2017) reported heritability values of 0.18 for SH and 0.25 for SL. These results imply that growth can potentially be improved by selective breeding.…”
Section: Resultssupporting
confidence: 91%
“…Consistent with similar studies carried out in related oyster species (Xu et al 2017;Vu et al 2020), heritability estimates based on SNP markers were higher for total weight than for growth-related morphometric traits (i.e. shell height, shell width and shell length).…”
Section: Growth Traits and Heritabilitysupporting
confidence: 88%
“…shell height, shell width and shell length). The estimation of heritability for total weight (herein referred to as TW) was similar to those reported for nine-month-old Portuguese oysters (ℎ 2 = 0.45) and a two-year old Pacific oyster strain (ℎ 2 = 0.42) (Vu et al 2021b;Xu et al 2017). Total weight, as measured in this study, is a composite phenotype made up of the animal's shell and soft tissue weights, in addition to the weight of any pallial fluid -thus is not a direct reflection of meat yield.…”
Section: Growth Traits and Heritabilitysupporting
confidence: 72%
“…), near‐black (h 2 = 0.52 ± 0.20 to 0.69 ± 0.16; Xu et al . ), and even purple, which was identified in some studies (see Song et al . for details on genetic differentiation).…”
Section: Geneticsmentioning
confidence: 84%